Do Exercise Trials for Hypertension Adequately Report Interventions? A Reporting Quality Study - Hacke, Claudia; Nunan, David; Weisser, Burkhard (International Journal of Sports Medicine, 2018)
Non-pharmacological treatment, including exercise, is an important therapy option for patients with hypertension. The study assessed the reporting quality of exercise-based interventions included in the latest meta-analysis on that topic in order to evaluate the transferability of findings into clinical practice. Reporting quality of 24 randomised controlled trials from a meta-analysis assessing blood pressure lowering effects of endurance training in 1,195 hypertensive patients was evaluated using TIDieR (Template for Intervention Description and Replication) and CERT (Consensus on Exercise Reporting Template) guidelines. Associations between reporting quality, publication year and impact factor of the publishing journals were examined. None of the studies described all intervention components completely. On average 61% (95%CI: 52-69) (TIDieR) and 57% (95%CI: 49-64) (CERT) of core items required for replication were reported. Frequent shortcomings were the reporting of adherence, intervention provider, and adverse events. Details about exercise dosage were missing in 22% (95%CI: 4-40). Publication year was related to the adherence to TIDieR (r=0.549, P=0.007) but not to CERT. No associations with journal impact factor were found. Reporting of exercise-based interventions for hypertension is not sufficient to allow for replication and limits translation of evidence into clinical practice. Researchers should apply, and review authors, journal editors and reviewers should check adherence to reporting guidelines.
Keywords: reporting quality; intervention studies; exercise therapy; hypertension; guideline